2021
DOI: 10.1016/j.mec.2021.e00182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel inhibitory metabolites and impact verification on growth and protein synthesis in mammalian cells

Abstract: Mammalian cells consume large amount of nutrients during growth and production. However, endogenous metabolic inefficiencies often prevent cells to fully utilize nutrients to support growth and protein production. Instead, significant fraction of fed nutrients is diverted into extracellular accumulation of waste by-products and metabolites, further inhibiting proliferation and protein synthesis. In this study, an LC-MS/MS based metabolomics pipeline was used to screen Chinese hamster ovary (CHO) extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Interestingly, negative impact on cell culture performance at two times spiking for group 2 (G2‐2×) was not as significant as three times spiking (G2‐3×, see Figure 5a–c). These findings were consistent with the results from another study which reported that spiking of NAP back into cell culture at millimolar level did not seem to show toxic effect on the growth of cells 7 . It was speculated that the observation as shown here, along with the data previously reported in other studies, suggested that NAP was re‐directed into the arginine metabolism pathway.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Interestingly, negative impact on cell culture performance at two times spiking for group 2 (G2‐2×) was not as significant as three times spiking (G2‐3×, see Figure 5a–c). These findings were consistent with the results from another study which reported that spiking of NAP back into cell culture at millimolar level did not seem to show toxic effect on the growth of cells 7 . It was speculated that the observation as shown here, along with the data previously reported in other studies, suggested that NAP was re‐directed into the arginine metabolism pathway.…”
Section: Resultssupporting
confidence: 93%
“…These findings were consistent with the results from another study which reported that spiking of NAP back into cell culture at millimolar level did not seem to show toxic effect on the growth of cells. 7 It was speculated that the observation as shown here, along with the data previously reported in other studies, suggested that NAP was re-directed into the arginine metabolism pathway. Specifically, NAP potentially can be converted back to putrescine which is a substrate from the polyamine At 3Â spiking level, however, the inhibitory effect of NAP on cellular performance was apparent, at cells realized a 16.2% decrease in VCD, 8.7% decrease in total IVCD and 17.6% decrease in peak growth rate (see Figure 5a-c).…”
Section: Phenotype Results Of Dose-dependent Nutrients Spiking Studysupporting
confidence: 78%
See 2 more Smart Citations
“…[13,14] In addition, media redesign or optimization benefits by fine-tuning certain media components to eliminate cellular bottleneck impacting the culture performance such as cell growth, viability, productivity, product quality and functionality. [15,16] It is largely affected by the frequent accumulation of inhibitory metabolites or toxic by-products, e.g., lactate and ammonia, due to the inefficient CHO cell metabolism, which can be alleviated by adjusting certain media components as a source of nutrients and growth factors such as amino acids, glucose, vitamins, and trace metals. [17][18][19] To provide an efficient manufacturing environment, each CHO cell culture medium typically contains 50-100 components, which are then tested and balanced with feed media using high-throughput experimental approaches.…”
Section: Introductionmentioning
confidence: 99%